Improving Family Independence in Hypertension Management through a Nursing Process Approach: A Case Study on Mrs I's Family in Garut Regency - Ridwan Rifai, Mohamad; Permana, Gin Gin Sugih; Daniati, Eva (CV. Literasi Publikasi Indonesia, 2025)
Family independence in managing hypertension is a key factor in achieving optimal quality of life. This study aims to improve the independence of Mrs I's family in Garut Regency through a family-based nursing process approach. The method used is a descriptive case study with data collection techniques including observation, interviews, documentation studies, and physical examinations. The results of the assessment showed that Mrs I's family was included in the Family Independence I (KM I) category, where they were aware of the problem of hypertension but did not understand the proper treatment. Nursing interventions focused on health education, medication management, and psychosocial support with a local cultural approach. Evaluation showed an increase in family independence to KM III, characterised by the family's ability to take preventive and promotive actions independently, such as routine control, low salt diet, and medication adherence. This study concludes that a contextualised family-based nursing approach involving active participation of family members is effective in improving the independence of hypertension management. The implication is that nurses need to master therapeutic communication and culture-based interventions to optimise community nursing practice